2020
DOI: 10.25259/ijmsr_4_2020
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Percutaneous Needle Tenotomy for Tendinosis

Abstract: Tendinosis is an important cause of musculoskeletal pain and disability. Tendinosis is principally a degenerative process, rather than inflammatory as was traditionally believed. Consequently, traditional tendinosis treatments focused solely on decreasing inflammation, i.e. intratendinous corticosteroid injection has often been ineffective. The advancement of ultrasonography as for the guidance of musculoskeletal intervention has facilitated the development of percutaneous procedures focused on the regenerativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…For example, DN coupled with autologous blood injection showed promising results under ultrasound guidance (VISA score: mean pre-procedure score = 39.8 (range 8-72) v mean post-procedure score = 74.3 (range 29-100), P < 0.001; mean follow up 14.8 months (range 6-22 months) (1). In another study, it has been reported that ultrasonography guided treatments facilitate the development of percutaneous procedures of regenerative healing in tendinopathy (55). The efficacy of DN under the guidance of sonography has been evaluated in several reported studies and found to be statistically significant for the treatment of tendinopathy, rotator cuff, and tendons around the greater trochanter (54).…”
Section: Discussionmentioning
confidence: 94%
“…For example, DN coupled with autologous blood injection showed promising results under ultrasound guidance (VISA score: mean pre-procedure score = 39.8 (range 8-72) v mean post-procedure score = 74.3 (range 29-100), P < 0.001; mean follow up 14.8 months (range 6-22 months) (1). In another study, it has been reported that ultrasonography guided treatments facilitate the development of percutaneous procedures of regenerative healing in tendinopathy (55). The efficacy of DN under the guidance of sonography has been evaluated in several reported studies and found to be statistically significant for the treatment of tendinopathy, rotator cuff, and tendons around the greater trochanter (54).…”
Section: Discussionmentioning
confidence: 94%